Green Synthesis and Characterization of Silver Nanoparticles from Nerium indicum and Investigation of Antioxidant and Anti-Cancerous Potential against Cervical Cancer Cell Line (HeLa) - Kini, Rutuja; Trivedi, Rashmi; Mujahid, Mohd Hasan; Patra, Pratikshya; Alharbi, S. A.; Alshammari, F. D.; Bealy, M. M. Babikir; Elkhalifa, A. E. O.; Siddiqui, Samra; Upadhyay, Tarun Kumar (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Nanotechnology has introduced innovative approaches to clinical applications and drug delivery systems, and among the various nano-materials, AgNPs have garnered significant attention due to their biocompatibility, antibacterial properties, and versatile applications in the medical field. A major cause of cancer related death in women and the fourth most prevalent malignancy worldwide is the cervical cancer, posing a pressing global health challenge. Materials and Methods: In our study, we employed a green synthesis approach to produce AgNPs using leaf extracts from NI and assessed their potential for both antioxidant and anticancer applications against cervical cancer (HeLa) cells. Characterization of the AgNPs was conducted using various techniques, including zeta-sizer, UV-vis spectrophotometry, and FTIR analysis. Results: The UV-Vis spectroscopy results revealed peak value between 400-500 nm, affirming the successful synthesis of the nanoparticles. These AgNPs exhibited an average particle size of 300.4 nm with a PDI value of 0.610. Scanning Electron Microscopy (SEM) image reveal that synthesized nanoparticles are spherical in morphology. Further, assessing the anticancer potential of the NI AgNPs, the MTT assay revealed an IC50 value of 165 μg/mL, indicative of their effective anticancer activity against cervical cancer cells. Haemolytic inhibition assay showed that at lower doses particles has more haemolytic inhibition potential. Furthermore, we evaluated their impact on cancer cells by examining ROS generation, nuclear morphology with Hoechst staining, and apoptosis of HeLa cells with PI staining. Additionally, we assessed mitochondrial and acidic organelles’ activity using MitoTracker and LysoTracker staining. Cell migration assay validated the inhibitory potential of NI AgNPs on the growth and migration of the cells. Conclusion: Our findings demonstrate that NI AgNPs possess notable potential as efficient anticancer agents against cervical cancer. This research underscores the promising role of green-synthesized AgNPs in the fight against cervical cancer and highlights their potential as a novel therapeutic strategy.
Keywords: Cytotoxicity; Nerium indicum; Silver nanoparticles; Cervical cancer; Haemolysis; Cell; migration